Dissertation Abstracts (Academy of Management Journal, 1964)
This article presents abstracts of studies related to management. They include “Some Determinants and Effects of Status Consensus,” by Frank Tobey Paine, “A Case Study of the Effect of Goal-Setting and Self-Control on Organization Performance,” by Anthony P. Raia, and “Inventory Management: Positive and Normative Models of Decision-Making in the Metals Service Center Industry,” by John D. Demaree.